PENGEMBALIAN BERKAS KLAIM PASIEN PESERTA JAMINAN KESEHATAN NASIONAL (JKN) DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE KOTA PONTIANAK - Andi Sulaimana; Andreasta Meliala; Julita Hendrartini (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2022)
Background: Approach of managed care in the National HealthInsurance Program (JKN) puts hospitals as a health facility referral with the prospective payment system. Treatment of patientsshould be done and handled in primary health facilities. Althoughthe number of patient referral to hospitals in JKN era remains high.The impact of the hospital is faced with an increase in claims billsto BPJS Kesehatan. By 2016 in RSUD Pontianak it was noted that6.98% of the income came from JKN hospital patients which had notbeen paid by BPJS Kesehatan, so some were returned. A researchneeds to be conducted on the cause of the returned claim file fromBPJS Kesehatan verifier to RSUD Pontianak.Objective: To find out the cause of the claims pending in RSUDPontianak.Methods: The research is an exploratory case study with a singlecase study design approach.Results: The claim process at RSUD Pontianak is still not as goodas never completed every month. Most of the causes of returnedclaims are administrative errors and medical reasons. Maladministration in the form of typing errors, dates, but a sign from thedoctor. Medical reasons include coding disagreements, differencesin perceptions about specific inspection directions, lack of support,differences in perceptions about secondary diagnostic inputs. Performance coding is limited to differences in perceptions betweenCoder and BPJS Kesehatan Verifier, positive physician responseto file claims reversed, BPJS Kesehatan Verifier perceptions areconstrained in capacity, differences in educational background, differences in understanding with Coder on Reselected Coding, anddifferences in regulatory implementation in the claims process.Conclusion: Technical error of claims administration process, difference of perception of coding, difference of comprehension aboutcomplementary examination, special treatment and secondary diagnosis input, and difference of perception to JKN regulation on verifier of cause of claim file of JKN patients return to RSUD Pontianak.